(untitled) (Gumilyov Journal of Pedagogy, 2026)
The formation of environmental responsibility among future teachers is considered one of the key conditions for achieving sustainable development goals within modern education systems. However, insufficient attention has been paid to pedagogical college students in Kazakhstan as a specific group of future educators responsible for shaping ecological culture and environmentally responsible behavior among schoolchildren. The purpose of this study is to assess environmental responsibility among pedagogical college students in Kazakhstan and to examine its relationship with participation in environmental initiatives and sustainable development competencies. The study involved 190 pedagogical college students who completed an online questionnaire designed to assess environmental attitudes, environmental behavior, and sustainable development competencies. The research methodology combined quantitative and qualitative approaches, including an author-developed questionnaire based on the conceptual principles of the New Ecological Paradigm (NEP) and Environmental Behavior Inventory (EBI), as well as semi-structured interviews. Statistical data processing was carried out using correlation analysis and exploratory factor analysis methods in SPSS Statistics 26.0. The results demonstrated generally positive environmental attitudes and moderate levels of environmental engagement among respondents. A statistically significant positive relationship was observed between environmental participation and sustainable development competencies. Behavioral activity was identified as the component most closely associated with sustainable development competencies and environmental responsibility. Gender and regional differences in environmental responsibility were also identified. The scientific novelty of the study lies in empirically demonstrating that environmental behavior is more closely associated with sustainable development competencies than environmental attitudes, identifying regional and gender differences in environmental responsibility, and providing one of the first empirical assessments of environmental responsibility among pedagogical college students in Kazakhstan. The practical significance of the study is related to the possibility of applying the obtained results in the modernization of teacher education programs, the integration of sustainable development principles into pedagogical curricula, and the development of educational policies aimed at strengthening environmental responsibility among future teachers.